Are Sanctions on Offenses Against Objects of Flora and Fauna Perfect? - O. M. Kalinina (Сибирское юридическое обозрение, 2020)
The article draws attention to the shortcomings of the construction of sanctions rules on crimes that infringe on the objects of flora and fauna. Taking into account the nature and degree of public danger, the acts of this group are classified by the legislator as crimes of small, medium gravity and serious crimes. The severity of the criminal act is indicated by the sanction of the criminal law norm. The analysis of the sanctions of this group of criminal acts showed that their design is far from perfect. The drawbacks are obvious both in the construction of single and alternative sanctions, as well as sanctions with an additional type of punishment. For example, when designing appropriate sanctions, the legislator equally often uses a fine and imprisonment; sanctions of the rules on crimes that infringe on flora and fauna are not all alternative; the degree of alternative is manifested in different ways; there is diversity in the legislator’s approaches to determining the number of additional penalties and their status in the framework of crimes of small gravity, medium gravity and serious crimes, as well as between these categories of criminal acts. According to the author, the legislator does not have clear criteria for designing sanctions, which undoubtedly negatively characterizes the quality of the criminal law in general.